Fama : The Politics of Talk and Reputation in Medieval Europe - Smail, Daniel Lord; Fenster, Thelma S. (Book collections on Project MUSE., 2003)
In medieval Europe, the word fama denoted both talk (what was commonly said about a person or event) and an individual's ensuing reputation (one's fama). Although talk by others was no doubt often feared, it was also valued and even cultivated as a vehicle for shaping one's status. People had to think about how to "manage" their fama, which played an essential role in the medieval culture of appearances.At the same time, however, institutions such as law courts and the church, alarmed by the power of talk, sought increasingly to regulate it. Christian moral discourse, literary and visual representation, juristic manuals, and court records reflected concern about talk. This book's authors consider how talk was created and entered into memory. They address such topics as fama's relation to secular law and the preoccupations of the church, its impact on women's lives, and its capacity to shape the concept of literary authorship.